6
$\begingroup$

I am recently struck upon this question that asks to find the sum until infinite terms $$\frac{1}{2\cdot 4}+\frac{1\cdot3}{2\cdot4\cdot6}+\frac{1\cdot3\cdot5}{2\cdot4\cdot6\cdot8}+.....∞$$ I tried my best to get something telescoping or something useful, but I failed. I even made a recurrence as $t_n=t_{n-1}\frac{2n-1}{2n+2}$, but this question was expected to be done with simple logic of series (Also that the recurrence on solving gives a higher order charasteristic polynomial, which might be difficult to solve without calculator). So, thus I ended up being confused with this question. So, can anyone prode a small solution to this (might be easy) problem .

$\endgroup$
12
$\begingroup$

While investigating the question, I found an easy answer., via telescoping series.: rearrange the fractions as $$\frac{1}{2\cdot 4}+\frac{1\cdot3}{2\cdot4\cdot6}+\cdots=\frac{1}{2}=\frac{1\cdot(4-3)}{2\cdot4}+\frac{1\cdot3\cdot(6-5)}{2\cdot4\cdot6}+\cdots$$ $$\frac{1\cdot4}{2\cdot4}-\frac{1\cdot3}{2\cdot4}+\frac{1\cdot3\cdot6}{2\cdot4\cdot6}-\frac{1\cdot3\cdot5}{2\cdot4\cdot6}\cdots=\frac{1}{2}$$

$\endgroup$
  • 2
    $\begingroup$ Excellently done. +1. $\endgroup$ – Balarka Sen Sep 18 '14 at 13:47
  • $\begingroup$ Clean and concise. My answer pales in comparison. (+1) $\endgroup$ – SuperAbound Sep 18 '14 at 13:48
4
$\begingroup$

$$\frac{1}{2\cdot 4}+\frac{1\cdot3}{2\cdot4\cdot6}+\cdots=\frac{1}{2}$$


Rewrite the sum as \begin{align} \frac{1}{2\cdot 4}+\frac{1\cdot3}{2\cdot4\cdot6}+\cdots &=\sum^\infty_{n=0}\frac{(2n+1)!!}{(2n+4)!!}\\ &=\sum^\infty_{n=0}\frac{(2n+1)!}{2^{2n+2}n!(n+2)!}\\ &=\sum^\infty_{n=0}\frac{1}{2n+2}\binom{2n+2}{n}x^{2n+2}\Bigg{|}_{x=1/2} \end{align} Differentiate once to get \begin{align} \frac{{\rm d}}{{\rm d}x}\sum^\infty_{n=0}\frac{1}{2n+2}\binom{2n+2}{n}x^{2n+2} &=\sum^\infty_{n=0}\binom{2n+2}{n}x^{2n+1}\\ &=\frac{1}{i2\pi}\oint_{|z|=1}\frac{x(1+z)^2}{z}\sum^\infty_{n=0}\left[\frac{(x+xz)^{2}}{z}\right]^n{\rm d}z\\ &=\frac{1}{i2\pi}\oint_{|z|=1}\frac{x(1+z)^2}{z-x^2(1+z)^2}{\rm d}z\\ &=\frac{1}{i2\pi}\oint_{|z|=1}\frac{x(1+z)^2}{-x^2z^2+(1-2x^2)z-x^2}{\rm d}z\\ &=-\frac{1}{i2\pi x^2}\oint_{|z|=1}\frac{x(1+z)^2}{(z-r_+)(z-r_-)}{\rm d}z\\ &=-\frac{1}{x^2}{\rm Res}\left[\frac{x(1+z)^2}{(z-r_+)(z-r_-)},r_+\right]\\ &=-\frac{1}{x}\frac{(1+r_+)^2}{r_+ - r_-} \end{align} We know that $r_+=\dfrac{1-2x^2-\sqrt{1-4x^2}}{2x^2}$. Coupled with the fact that $r_+ - r_- =\dfrac{-\sqrt{1-4x^2}}{x^2}$, this gives us \begin{align} \sum^\infty_{n=0}\binom{2n+2}{n}x^{2n+1} &=\frac{\sqrt{1-4x^2}}{4x^3}-\frac{1}{2x^3}+\frac{1}{4x^3\sqrt{1-4x^2}} \end{align} Now, integrate this expression once \begin{align} \sum^\infty_{n=0}\frac{1}{2n+2}\binom{2n+2}{n}x^{2n+2} &=\frac{1-\sqrt{1-4x^2}}{4x^2}+C \end{align} It is easy to see that \begin{align} C =\lim_{x\to 0}\frac{\sqrt{1-4x^2}-1}{4x^2} =\lim_{u\to 1}\frac{u-1}{1-u^2} =-\lim_{u\to 1}\frac{1}{1+u} =-\frac{1}{2} \end{align} Finally, letting $x=\dfrac{1}{2}$ yields \begin{align} \sum^\infty_{n=0}\frac{(2n+1)!!}{(2n+4)!!} &=\frac{1-\sqrt{1-1}}{1}-\frac{1}{2}\\ &=\frac{1}{2} \end{align}

$\endgroup$
  • 1
    $\begingroup$ Actually, the result follows almost immediately if you recognize the series at line $3$ as Lagrange-Burmann inversion for $f(z)=(1+z)^2$ or some such. $\endgroup$ – Balarka Sen Sep 18 '14 at 13:35
  • $\begingroup$ @BalarkaSen That is interesting to know. I was unaware of the existence of such a formula and it seems like I used a sledgehammer to kill a fly. $\endgroup$ – SuperAbound Sep 18 '14 at 13:48

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.